Facial Nerve Schwannomas of the Cerebellopontine Angle: The Mayo Clinic Experience - Jacob, Jeffrey T.; Driscoll, Colin L. W.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Background There is often controversy regarding the optimal management for patients with facial nerve schwannomas (FNSs) of the cerebellopontine angle (CPA).Methods The clinical and radiological outcomes in 14 patients with CPA FNS were retrospectively reviewed.Results Patients underwent resection with anatomic nerve preservation (n = 3), facial-hypoglossal nerve anastomosis (n = 4), gamma knife radiosurgery (GKS) (n = 6), or observation (n = 1). A total of 83% of tumors that underwent GKS were stable or decreased in size. No patient who underwent resection showed evidence of tumor recurrence; the tumor under observation remained unchanged with normal facial function at the time of the last follow-up. Facial function was decreased in 57%, stable in 14%, and improved in 29% of those who underwent microsurgery. A total of 67% of patients who underwent GKS had stable facial function. Serviceable hearing was maintained in 50% of patients in the GKS group and 67% of the tumor resection group. Mean and median follow-up was 48 and 43 months, respectively (range, 12 to 95 months).Conclusion Observation should be the primary management when encountered with FNS of the CPA in those with good neurologic function. Microsurgery or radiosurgery may be used in those with poor facial function or tumor progression.
Keywords: facial nerve; schwannoma; cerebellopontine angle; vestibular schwannoma